Economics education from scratch: a view from post-communist Romania. (19th October 2009) - Cojanu, Valentin; Nicolae, Mariana; Maniu, Mircea
Two decades elapsed since economics had to replace Marxist political economy and be taught from scratch. This paper gives an account of the consequences and implications of this process in career advancement, research output, and teaching experiences for the economics community in Romania. Our study also parallels the proposed reforms with the international experience in the field of evaluating academic and research performance.